2004
DOI: 10.1074/jbc.m404470200
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Amino Acid Transporter AAT-9 of Caenorhabditis elegans Localizes to Neurons and Muscle Cells

Abstract: The Caenorhabditis elegans genome encodes nine homologues of mammalian glycoprotein-associated amino acid transporters. Two of these C. elegans proteins (AAT-1 and AAT-3) have been shown to function as catalytic subunits (light chains) of heteromeric amino acid transporters. These proteins need to associate with a glycoprotein heavy chain subunit (ATG-2) to reach the cell surface in a manner similar to that of their mammalian homologues. AAT-1 and AAT-3 contain a cysteine residue in the second putative extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The Wormbase expression patterns come primarily from multiple microarray experiments, and we paid close attention to expression patterns related to sperm or the germline. Two genes are involved in oogenesis ( aat-9 and car-1 ), but both also function in non-germline tissues [34][35]. Two other genes, T24B1.1 and W06D4.2, were of particular interest.…”
Section: Resultsmentioning
confidence: 99%
“…The Wormbase expression patterns come primarily from multiple microarray experiments, and we paid close attention to expression patterns related to sperm or the germline. Two genes are involved in oogenesis ( aat-9 and car-1 ), but both also function in non-germline tissues [34][35]. Two other genes, T24B1.1 and W06D4.2, were of particular interest.…”
Section: Resultsmentioning
confidence: 99%
“…In fact L-Tyr becomes an essential amino acid in patients with PKU (58). However, amino acid transporters in C. elegans do not saturate by L-Phe as easily as in mammals; i.e., the transporter AAT-9, which localizes in neurons and muscle cells, presents a value of K m Ն 0.7 mM for L-Phe (59). This might explain the absence of neurological defects in the pah-1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…AAT-4 through AAT-9 are the least homologous to LAT1 and show 23–29% homology to AAT-1 through AAT-3. Additionally, AAT-4 through AAT-9 do not form complexes with the glycoprotein heavy chain subunit, which is required for AAT-1, AAT-3, and LAT1 (Kanai and Endou, 2003; Veljkovic et al, 2004a; Veljkovic et al, 2004b). Our studies indirectly examined whether AAT-6 is involved in MeHg toxicity by examining the knockdown of nrfl-1 .…”
Section: Discussionmentioning
confidence: 99%
“…However the function of these transporters has not been characterized in the worm in vivo . AAT-4 through AAT-9 have the least homology to human LAT1 and do not contain the cysteine residue required for bonding with the heavy chain (Veljkovic et al, 2004a). Recently it has been reported that AAT-6 interacts with the scaffold protein Na + /H + exchanger regulatory factor, NRFL-1, to localize to the membrane (Hagiwara et al, 2012), but it has not been reported whether NRFL-1 is required for other AAT proteins as well.…”
Section: Introductionmentioning
confidence: 99%